User interface for elaboration theory based on adept model / Jamilah Adam - Adam, Jamilah (2005)
The emergent of World Wide Web in 1992 as a telecommunication tool has revolutionized how to teach and learn. It makes e-learning increasing accessible and many learning institutes have adapted to e-learning. Experiences with development of user interface (Ul) projects for e-learning indicated a need for additional flexibility and speed applying new technologies to future products. Learner satisfaction is most important criteria to imply in design and developing Ul. The paper discusses of Ul that can influence learning and teaching process in e-learning medium for high education. More features are including to Ul towards to hypermedia era. This study to develop prototype user interface (Ul) for Data Communication subjects offered in Faculty of Information technology and Quantitative Science (FITQS). The Elaboration Theory and the Advanced Design Environments for Prototyping with Tasks Models (ADEPT) are used to develop this Ul. The method used in this studies by conduct observation on 20 students which consist 16 females and 4 males of 18 to 25 years old in FITQS. This observation is conduct during their laboratory session that takes two hours. Second method is interviews two of lecturers are involved teaching Data Communication in the same faculty. Last method, we study five of existing web course. Through this gathered information, researcher indicates that when using more Ul tools, its can influence student learning and make them enjoy this activity.